2021
DOI: 10.1021/acs.joc.1c00229
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Mulberry Diels–Alder-Type Adducts Kuwanons G and H

Abstract: Mulberry Diels−Alder-type adducts (MDAAs) are a group of rare natural polyphenols biosynthetically derived from [4 + 2]-cycloaddition of chalcones and dehydroprenylphenols. In this study, kuwanons G (1) and H (2), two bioactive MDAAs with unique dehydroprenylflavonoid dienes, were totally synthesized for the first time in a biomimetic manner. The key features of the convergent route include the use of the Baker−Venkataraman rearrangement, alkylation of β-diketone, intramolecular cyclization, and Suzuki−Miyaura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…Although the total synthesis of natural compounds is not covered in the present review, many of the procedures described have been utilized to prepare natural DA adducts and analogs. [128][129][130][131][132][133][134][135][136]…”
Section: Chalcones As Dienophilesmentioning
confidence: 99%
“…Although the total synthesis of natural compounds is not covered in the present review, many of the procedures described have been utilized to prepare natural DA adducts and analogs. [128][129][130][131][132][133][134][135][136]…”
Section: Chalcones As Dienophilesmentioning
confidence: 99%
“…In 2021, the Tang group reported a convergent route towards the total synthesis of two MDAAs named kuwanons G and H (92 and 93) with unique dehydroprenylflavone dienes. The key features of this approach included the use of Baker-Venkataraman rearrangement, alkylation of β-diketone, intramolecular cyclization, and Suzuki-Miyaura coupling to achieve the unstable dehydroprenylflavone diene [194].…”
Section: Total Syntheses Of Kuwanons G and Hmentioning
confidence: 99%
“…In 2021, Luo et al reported the total synthesis of kuwanons G and H ( 11 and 12 ), two DAAs derived from the condensation of a chalcone with a flavone diene, that differs only in the presence of a prenyl group in kuwanon H ( 12 ) [ 95 ]. According to the retrosynthetic plan reported in Figure 48 , kuwanons G and H ( 11 and 12 ) could be obtained from the demethylation of methoxy groups of heptamethyl ether precursors 144 or 145 , which, in turn, could be prepared from Diels–Alder cycloaddition of diene 29 with 2′-hydroxychalcones 24 or 86 as dienophiles.…”
Section: Total Synthesis Of Mulberry Daasmentioning
confidence: 99%